ANALISIS RESPONS TINGKAH LAKU IKAN PEPETEK (Secutor insidiator) TERHADAP INTENSITAS CAHAYA BERWARNA - EVA UTAMI (Akuatik: Jurnal Sumberdaya Perairan, 2009)
Light is one of the artificial stimuli to attract and concentrate fish on the catchable area. Each fish species can recognize a particular wavelength by photo pigment in its retina. The influence factors to retinal adaptation are color light, light intensity and time of exposure. Fish retinal adaptation on light is indicated by change of cone cell movement level. The objectives of this research were to reveal pattern of ponyfish reaction toward blue and red color light. Experiment was carried out in Pelabuhan Ratu Bay and Fish Culture Laboratory at Bogor Agricultural University, November 2005 to January 2006. The results indicated that ponyfish is fototaxis fish and more perceive blue light than red color light. Light intensity has an effect on rise number of fish schooling.